PENERAPAN METODE TOPOGRAFI MENGGUNAKAN GPS-GEODETIK DENGAN METODE RTK (REAL TIME KINEMATIK) DI PT SENA WILAYAH CEMPAKA PUTIH - Untung Surapati; Saldy Michael (CKI ON SPOT, 2021)
Many of the government and private agencies aredeveloping geodetic GPS technology, for engineeringand research needs, mapping related to position. CORSis an active geodetic frame network in the form of apermanent station equipped with a receiver that canreceive signals from GPS satellites and other satellitegnss, which operate continuously for twenty-four hours.so that the function of CORS can later be used insituation mapping using the RTK method (real timekinematics). PT. SENA is one of the private companiesengaged in engineering that provides technical servicesin the oil and gas industries such as pipes, mechanicalprocesses, electricity, geodetics, civil engineering, andtelemetry. Our services here include surveys, technicalresearch, feed tip design and detailed engineeringdesign, project management consulting, technicalinspection and testing, commissioning and other postoperations.the problem at pt.sena currently does nothave a topographic mapping team. The purpose of theresearch is to make topographic mapping using theGPS geodetic RTK method, which later topographicmaps can be used such as land acquisition, buildingrehabilitation, road.